ANALISIS PENGARUH KESADARAN HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK PERSONAL CARE STUDI EKSPERIMEN PADA MAHASISWA UNIVERSITAS LAMPUNG - Jenny Ayu Mutia; Suprihatin Ali; Iqbal Harori (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine the effect of halal awareness on purchasing decisions for personal care products. This research uses an experimental research type with a quantitative approach. The research method used is verification or causality method to test the hypothesis in this study. The population of this study were students of the University of Lampung. The sampling technique used purposive sampling with a sample of 100 respondents. Respondents must be active students at the University of Lampung who buy their own personal care products. The data was obtained from an online questionnaire using a Likert scale. The results showed that the respondents had high halal awareness. From data analysis using a simple linear regression method, the halal awareness variable has a moderate relationship and has a significant effect on purchasing decisions by 54.7%, the rest is explained by other factors. For this reason, the development of research measuring instruments, the use of more specific research demos, and the one-group pretest-posttest design method to obtain more accurate data results. Companies can also continue to improve product quality by including and continuously updating halal logos and labels to increase consumer confidence in buying halal personal care products.